Anti-amphiphysin I antibodies in patients with paraneoplastic neurological disorders associated with small cell lung carcinoma. Issue 2 (1st February 1999) - Saiz, A; Dalmau, J; Butler, M Husta; Chen, Q; Delattre, J Y; De Camilli, P; Graus, F
Abstract : Patients with stiff man syndrome and breast cancer develop anti-amphiphysin I antibodies that primarily recognise the C terminus of the protein. Anti-amphiphysin I antibodies have also been identified in a few patients with paraneoplastic neurological disorders (PND) and small cell lung cancer (SCLC). The frequency of anti-amphiphysin I antibodies in patients with SCLC and PND was analysed and the epitope specificity of these antibodies was characterised.  Anti-amphiphysin I antibodies were evaluated by immunohistochemistry on human and rat cerebellum and immunoblots of rat brain homogenates. Serum samples included 134 patients with PND and anti-Hu antibodies (83% had SCLC), 44 with SCLC and PND without antiHu-antibodies, 63 with PND and either Yo, Ri, or Tr antibodies, 146 with SCLC without PND, and 104 with non-PND. Positive serum samples were confirmed with immunoblots of recombinant human amphiphysin I and immunoreacted with five overlapping peptide fragments covering the full length of the molecule.  Serum samples positive for anti-amphiphysin I antibodies included those from seven (2.9%) patients with PND and two (1.4%) with SCLC without PND. Six of the seven anti-amphiphysin I antibody positive patients with PND had SCLC (three with Hu-antibodies), and one had anti-Hu-antibodies but no detectable tumour. The PND included encephalomyelitis/sensory neuropathy (five patients), cerebellar degeneration (one), and opsoclonus (one). All anti-amphiphysin I antibodies reacted with the C terminus of amphiphysin I, but seven also recognised other fragments of the molecule.  In conclusion, anti-amphiphysin I antibodies are present at low frequency in patients with SCLC irrespective of the presence of an associated PND. All anti-amphiphysin I antibody positive serum samples have in common reactivity with the C terminus of the protein.